CONFUSION AND DENIAL: NEED FOR SYSTEMS THINKING TO UNDERSTAND THE HIV EPIDEMIC IN PAKISTAN - Abdullah, Muhammad Ahmed; Shaikh, Babar Tasneem (Journal of Ayub Medical College Abbottabad, 2014)
The first case of HIV appeared in Pakistan more than 25 years ago, and since then the prevalence of the disease is creeping up apparently at a dawdling pace, with only 3,983, cases registered till November 2010, of which 1,725 are undergoing treatment. The National AIDS Control Program is responsible for managing the epidemic. Pakistan has moved from a ’˜low prevalence-high risk’ to a ’˜concentrated epidemic’ state, yet the forcefulness required for managing this silent escalation of HIV infected numbers is not being highlighted, as it should be. A more holistic focus is the need of the hour, and for this purpose the WHO’s HealthSystemsBuildingblocks have been used to discuss the state of affairs in Pakistan, with reference to the HIV/AIDS concentrated epidemic. This paper attempts to present a narrative, based on extensive literature review, with a focus on the six building blocks of health systems strengthening. No doubt, the service delivery has to be responsive; but skilled human resources, a robust information system, an uninterrupted supplies and use of latest technology, adequate financing, and above all good governance at operational level are essential ingredients, which call for re-orienting the national programme today. Lack of coordination, capacity and interventions with questionable sustainability pave a perilous path. Hitherto the issue can be addressed by involving stakeholders from all levels of the society and managing the void between policy and implementation. Furthermore, interventions that focus on the long term future are imperative to combat the menace threatening the human lives. Keywords: HIV/AIDS; Pakistan; Health system; Building blocks